Vitamin B12 and folate decrease inflammation and fibrosis in NASH by preventing syntaxin 17 homocysteinylation - Tripathi, Madhulika; Singh, Brijesh Kumar; Zhou, Jin; Tikno, Keziah; Widjaja, Anissa; Sandireddy, Reddemma; Arul, Kabilesh; Abdul Ghani, Siti Aishah Binte; Bee, George Goh Boon; Wong, Kiraely Adam; Pei, Ho Jia; Shekeran, Shamini Guna; et al. (Journal of hepatology, 2022)
Several recent clinical studies have shown that serum homocysteine (Hcy) levels are positively correlated, while vitamin B12 (B12) and folate levels are negative correlated, with non-alcoholic steatohepatitis (NASH) severity. However, it is not known whether hyperhomocysteinemia (HHcy) plays a pathogenic role in NASH. We examined the effects of HHcy on NASH progression, metabolism, and autophagy in dietary and genetic mouse models, patients, and primates. We employed vitamin B12 (B12) and folate (Fol) to reverse NASH features in mice and cell culture. Serum Hcy correlated with hepatic inflammation and fibrosis in NASH. Elevated hepatic Hcy induced and exacerbated NASH. Gene expression of hepatic Hcy-metabolizing enzymes was downregulated in NASH. Surprisingly, we found increased homocysteinylation (Hcy-lation) and ubiquitination of multiple hepatic proteins in NASH including the key autophagosome/lysosome fusion protein, Syntaxin 17 (Stx17). This protein was Hcy-lated and ubiquitinated, and its degradation led to a block in autophagy. Genetic manipulation of Stx17 revealed its critical role in regulating autophagy, inflammation and fibrosis during HHcy. Remarkably, dietary B12/Fol, which promotes enzymatic conversion of Hcy to methionine, decreased HHcy and hepatic Hcy-lated protein levels, restored Stx17 expression and autophagy, stimulated β -oxidation of fatty acids, and improved hepatic histology in mice with pre-established NASH. HHcy plays a key role in the pathogenesis of NASH via Stx17 homocysteinylation. B12/folate also may represent a novel first-line therapy for NASH. The incidence of non-alcoholic steatohepatitis, for which there are no approved pharmacological therapies, is increasing, posing a significant healthcare challenge. Herein, based on studies in mice, primates and humans, we found that dietary supplementation with vitamin B12 and folate could have therapeutic potential for the prevention or treatment of non-alcoholic steatohepatitis. [Display omitted] •Hyperhomocysteinemia is positively associated with NASH progression.•Increased intrahepatic homocysteine causes NASH.•STX17 homocysteinylation and ubiquitination leads to a block in autophagy during NASH progression.•Supplementary vitamin B12 and folate restore STX17 expression and autophagy to decrease inflammation and fibrosis in NASH.